The hundred secret senses - Tan, Amy. (New York : Ivy Books, 1996)
Kwan moves from China to live with her family in San Francisco and develops a relationship with her half sister Olivia, confiding in Olivia about the ghosts who advise her about love and relationships.
School Library Journal.
Wilson's Fiction.
Wilson's Senior High School.
Adult
Keywords: Chinese American women -- Fiction; Sisters -- United States -- Fiction; Chinese American women -- Fiction; Domestic fiction; Sisters -- Fiction; China -- Fiction; China -- Fiction